Effect of water temperature increase on HO-1 expression in European sea bass (Dicentrarchus labrax L.) tissues - Hachfi, L.; Simide, R.; Richard, S.; Couvray, S.; Coupé, S.; Gaillard, S.; Pierre, S.; Grillasca, J. P.; Prevot-d'alvise, N. (Cellular and Molecular Biology, 2012)
One of the most pertinent environmental factors influencing the marine organism life is temperature. It has been demonstrated that an increase of temperature is able to induce the synthesis of heat shock proteins (HSP). In this study we investigated the expression of HO-1 mRNA, also referred to as HSP32, in different tissues of European sea bass (Dicentrarchus labrax, L.) at several time points after increased temperature exposure (from 12°C to 30°C). Our results showed that HO-1 was not expressed in gills, heart, muscle and brain while it was expressed at a basal level in intestine. In liver, spleen and kidneys, HO-1 expression was influenced by temperature increases. In the spleen, we found a significant decrease of the HO-1 expression at the end of 4 weeks. In kidneys a very fast collapse of HO-1 expression level was recorded reaching null value as soon as one hour after exposure to 30°C. In liver, HO-1 expression increased from one hour of exposure to 30°C confirming HO-1 involvement to heat shock response in this organ. This increasing trend reached a 4.5-fold higher value than the initial level after 4 weeks.